Detectable viral load associated with unmet mental health and substance use needs among trans women living with HIV in San Francisco, California - Erin C. Wilson; Glenda N. Baguso; Jerry Quintana; Bow Suprasert; Sean Arayasirikul (BMC, 2024)
Abstract Background Substance use and mental distress are known barriers to HIV care engagement among trans women. Less is known about access and utilization of mental health and substance use care among trans women and the relationship between unmet behavioral health needs and HIV viral suppression. We examined the relationship between mental health and substance use on HIV viral load among trans women living with HIV. We also examined the relationship between mental health and substance use services needs with HIV care engagement and having a detectable viral load by comparing engagement in care cascades. Methods Data are from a 2022 baseline assessment for an intervention with trans women living with HIV (n = 42) in San Francisco. Chi-Squared or Fisher's exact tests were conducted to determine associations between HIV viral load, mental health, and substance use. We also examine characteristics associated with each step in the HIV, mental health, and substance use care cascades. Results Most participants were trans women of color (85.7%), 40 years of age or older (80.9%), with low income (88.1%), and almost half were unstably housed (47.6%). Of the 32 participants who screened positive for depression, anxiety and/or psychological distress, 56.3% were referred for mental health services in the past 12 months. Of those who were referred, 44.4% received mental health services. Of the 26 participants who screened positive for a substance use disorder, 34.6% were referred to substance use services in the past 12 months. Of those referred, 33.3% received substance use services in the past 3 months. Latina trans women had a low referral rate to meet their mental health needs (50%) and only 16.7% of African American/Black trans women who screened positive for a substance use disorder were referred for services, while trans women of other race/ethnicities had high referral and services utilization. No significant results were found between HIV viral load and screening positive for a mental health disorder. Methamphetamine use was statistically associated with having a detectable HIV viral load (p = 0.049). Conclusions We identified significant unmet mental health and substance use services needs and noted racial/ethnic disparities in the context of high HIV care engagement among trans women living with HIV. We also found that methamphetamine use was a barrier to having an undetectable viral load for trans women living with HIV. To finally end the HIV epidemic, integration of behavioral health screening, linkage, and support are needed in HIV care services for populations most impacted by HIV, especially trans women. Trial registration NCT, NCT 21-34,978. Registered January 19, 2022.